TRANSMISSION-TRANSFORMATION OF MURATTAL AND MUJAWWAD OF THE QUR’AN IN THE DIGITAL ERA: AN ANALYSIS OF AHMAD RAFIQ’S LIVING QUR’AN - Rais Nasruddin, M. (International Journal of Multidisciplinary Reseach, 2026)
The number of murattal and mujawwad of the Qur’an applications today result in different transmission and transformation before the entry of the digital era. This shows one of the phenomena of the Qur’an that